Phosphorus Vacancies as Effective Polysulfide Promoter for High‐Energy‐Density Lithium–Sulfur Batteries. Issue 12 (10th February 2022) - Sun, Rui; Bai, Yu; Bai, Zhe; Peng, Lin; Luo, Min; Qu, Meixiu; Gao, Yangchen; Wang, Zhenhua; Sun, Wang; Sun, Kening
Abstract: Lithium–sulfur batteries have aroused great interest in the context of rechargeable batteries, while the shuttle effect and sluggish conversion kinetics severely handicap their development. Defect engineering, which can adjust the electronic structures of electrocatalyst, and thus affect the surface adsorption and catalytic process, has been recognized as a good strategy to solve the above problems. However, research on phosphorus vacancies has been rarely reported, and how phosphorus vacancies affect battery performance remains unclear. Herein, CoP with phosphorus vacancies (CoP‐Vp) is fabricated to study the enhancement mechanism of phosphorus vacancies in Li–S chemistry. The derived CoP‐Vp features a low Co‐P coordination number and the introduced phosphorus vacancies mainly exist in the form of clusters. The obtained CoP‐Vp can reinforce the affinity to lithium polysulfides (LiPSs) and thus the shuttle effect can be restrained. In addition, the reduced reaction energy barriers and the promoted diffusion of Li + can accelerate redox kinetics. Electrochemical tests and in situ Raman results confirm the advantages of phosphorus vacancies. The S/CNT‐CoP‐Vp electrode presents outstanding cycling performance and achieves a high capacity of 8.03 mAh cm −2 under lean electrolyte condition ( E /S = 5 μLE mg −1 S ). This work provides a new insight into improving the performance of Li–S batteries through defect engineering. Abstract : Cobalt phosphide with phosphorus vacancies is designed and used as a sulfur host for Li–S batteries. The introduction of phosphorus vacancies can adjust electronic structures, and thus enhance the chemical affinity to lithium polysulfides and accelerate the redox kinetics for polysulfide conversions. The batteries can exhibit excellent electrochemical performance under high sulfur loadings and lean electrolyte conditions.